2005
DOI: 10.1021/bc050097k
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Lipophosphoramidates and Lipophosphoguanidines Are Very Efficient for in Vivo DNA Delivery

Abstract: Two new families of cationic lipids were designed and synthesized for gene delivery, namely "lipophosphoramidates" and "lipophosphoguanidines", whose efficiency was noteworthy. The most efficient have an arsonium cation as the polar head, and the unsaturated lipidic tails (e.g. oleyl) gave the better in vivo results (mice lungs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 13 publications
(3 reference statements)
3
61
0
Order By: Relevance
“…Solvents were freshly distilled on appropriate drying agents (CH 2 Cl 2 was distilled over P 2 O 5 , DIPEA was distilled over NaOH), and reactions were run under nitrogen. All compounds were fully characterised by 1 H (500 MHz), 13 C (100 MHz) and 31 P (121.49 MHz) NMR spectroscopy (Bruker AC 300 and Advance DRX 500 spectrometers). Coupling constants (J) are given in Hertz.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Solvents were freshly distilled on appropriate drying agents (CH 2 Cl 2 was distilled over P 2 O 5 , DIPEA was distilled over NaOH), and reactions were run under nitrogen. All compounds were fully characterised by 1 H (500 MHz), 13 C (100 MHz) and 31 P (121.49 MHz) NMR spectroscopy (Bruker AC 300 and Advance DRX 500 spectrometers). Coupling constants (J) are given in Hertz.…”
Section: Methodsmentioning
confidence: 99%
“…Coupling constants (J) are given in Hertz. When needed, 13 C heteronuclear HMQC and HMBC were used to establish structures unambiguously. Mass spectroscopy analyses were performed by CRMPO (UniversitØ de Rennes 1, Rennes, France) with a MS/MS high-resolution Micromass ZABSpec-TOF.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our own experiments with the phosphonolipids family, showed that the substitution of an ammonium with a phosphonium or an arsonium polar head results in increased efficacy (up to seven times depending on the cell model used) and reduced toxicity. As an example, the lipophosphoramidate, KLN47, with an arsonium polar head group and two oleic chains gave higher transfection results in mice lungs after intravenous injection (IV) than the homologous ammonium compound GL73 [22,23]. Modifications effecting the nature of the fatty chains were also performed.…”
Section: The Development Of Monocationic Lipids For Use In Gene Delivmentioning
confidence: 99%
“…Several structural modifications were performed including variations of the hydrophobic chain length (Le Bolc'h et al 1995;Floch et al 1998), the structure of the linker and of the polar head group Mevel et al 2007). An interesting structural modification was the substitution of the trimethylammonium polar head group by either a trimethylphosphonium or a trimethylarsonium, to decrease the toxicity of the cationic lipids Guenin et al 2000;Picquet et al 2005). The rationale for this was based on a previous study that had used a similar strategy (Stekar et al 1995) and on the fact that trimethylarsonium groups have been found in natural phospholipids (arsenocholine) from marine organisms (Junk et al 1990).…”
Section: Natural Lipid From Plasma Membranementioning
confidence: 99%